PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERBANKAN SELAMA MASA PANDEMI (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2020-2021) - Melati Achyar Pulungan; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2022)
The purpose of this study is to examine the effect of the application of Good Corporate Governance on the financial performance of banks. This type of research is a type of quantitative research. This study uses secondary data obtained from annual reports of banking companies (annual reports) listed on the Indonesia Stock Exchange (BEI). Data were analyzed using multiple regression analysis with the help of the SPSS 2022 program.The results of this study indicate (1) The Board of Directors has a positive and insignificant effect on Banking Financial Performance. (2) The Independent Board of Commissioners has a positive and insignificant effect on Banking Financial Performance.  (3) The Audit Committee has a negative and insignificant effect on Banking Financial Performance. (4) Ownership Structur has a positive and significant effect on Banking Financial Performance. (5) Foreign Ownership has a positive and insignificant effect on Banking Financial Performance. (6) Company size has a positive and insignificant effect on Banking Financial Performance.(7)External Audit Quality has a positive and insignificant effect on Banking Financial Performance.